46 - QUALITY OF LIFE OF NEEDED INTELLECTUAL DANCE PRACTITIONERS II (Fiep Bulletin - online, 2023)
Enabling the importance of dance, capable of feeling enchantment and magic, feeling the movements, mastering the rhythm, feeling the emotions and feelings in the choreography and free dance is that we built this work whose objective was to understand the quality of life of people with knowledge that need to practice dancing. Sample of this study is from APAE dance, Campina Grande – PB, that responds to 2 special people, whose analysis was of quality care. This is a descriptive exploratory study, which used as statistical methods the Excel program for Windows 10, presented in the form of tables and graphs, by average and percentage. In all the variables that became evident and very important in the amounts studied, concluding that it is this activity proposed as people with special importance.